Lagrangian descriptors: The shearless curve and the shearless attractor - Simile Baroni, R. [UNESP]; De Carvalho, R. Egydio [UNESP] (American Physical Society (APS), 2024)
Hamiltonian systems with a nonmonotonic frequency profile are called nontwist. One of the key properties of such systems, depending on adjustable parameters, is the presence of a robust transport barrier in the phase space called the shearless curve, which becomes the equally robust shearless attractor when dissipation is introduced. We consider the standard nontwist map with and without dissipation. We derive analytical expressions for the Lagrangian descriptor (LD) for the unperturbed map and show how they are related to the rotation number profile. We show how the LDs can reconstruct finite segments of the invariant manifolds for the perturbed map. In the conservative case, we demonstrate how the LDs distinguish the chaotic seas from regular structures. The LDs also provide a remarkable tool to identify when the shearless curve is destroyed: we present a fractal boundary, in the parameter space, for the existence or not of the shearless torus. In the dissipative case, we show how the LDs can be used to localize point attractors and the shearless attractor and distinguish their basins of attraction.